PRESTASI BELAJAR SISWA DITINJAU DARI INTENSITAS MENGGUNAKAN GADGET DAN MINAT BACA NON E-BOOK - Merly Erlina; Mistety Oktaviana; Erdina Indrawati; RR. Dini Diah Nurhadianti (Jurnal Pendidikan (Teori dan Praktik), 2022)
This study aims to determine the effect of the use of gadgets on reading interest in 8th grade students of SMPN 3 Tangerang Banten. The number of subjects in this study were 175 people. The research method in this study is a quantitative method. Based on the results of the analysis of research data using multiple regression techniques, it can be said that the multiple linear regression equation also shows that the variable intensity of using gadgets has a negative influence on learning achievement and interest in reading non-e-book books has a positive influence on learning achievement. This is shown through the regression results Y=87.528-0.049X1+0.007X2. Based on the regression model, the constant (a) is 87,528, meaning that if the intensity of using gadgets (X1) and interest in reading non-e-books (X2) is zero, then learning achievement is 87,528. Then the coefficient value of the intensity of the use of the device is -0.049, meaning that if the intensity of the use of the device has increased by one percent, the learning achievement has decreased by 0.049 percent with the condition that the other independent variables are eligible to remain. While the coefficient of interest in reading non-e-book books is 0.007, meaning that if interest in reading non-e-books has increased by one percent, learning achievement will increase by 0.007 percent with the condition that other variables are feasible. .   Keywords: Use of Devices, Interest in Reading e-Books, Learning Achievement, Grade 8